Development and Application of a Trichoderma-PGPR Bioformulation to Enhance Rice Growth - Waraporn Sutthisa; Juthatip Srilawong; Nattawut Kliangros; Surasak Khankhum; Punyisa Charirak (Journal of Pure and Applied Microbiology)
This study aimed to develop and evaluate a bioformulation combining Trichoderma asperellum MSU007 and the plant growth-promoting rhizobacterium (PGPR) Bacillus velezensis MSU01 to enhance rice growth. Coexistence assays demonstrated that T. asperellum MSU007 and the PGPR B. velezensis MSU01 could grow concurrently without mutual inhibition. A powdered bio-formulation was created that showed effective water solubility and moisture content stability across the three formulations. Viability assessments indicated that T. asperellum MSU007 and the PGPR maintained high survival rates over a 60 day storage period, with formulation 3 (T. asperellum MSU007 and B. velezensis MSU01 at a 3:1 ratio) consistently exhibiting the highest viability. The effect of the bioformulation on rice growth was significant. Formulation 3 was the most effective in enhancing rice seed germination and seedling growth. It achieved 100% germination by the fourth day and consistently promoted improvements in shoot and root lengths, as well as in the fresh and dry weights of shoots and roots. Formulations 1 and 2 also showed positive effects but were less effective than formulation 3. In summary, the Trichoderma-PGPR bioformulations, particularly formulation 3, significantly enhanced rice growth, offering a promising solution for improving crop yield.